A monitoria no curso de pedagogia da Universidade Federal do Ceará: entre a especialidade técnica e a formação docente na década de 1970 - Chaves, Flávio Muniz (2014)
The research was the result of a problem experienced during graduation : the lack of documents to tell , even a little about the history of the Faculty of Education . After a brief search in the Humanities Center of the UFC and hearing the older teachers of the Faculty of Education Library - FACED - I realized that there is only a dissertation of 1990 on the history of the Faculty of Education at the UFC . The focus of this research is to understand how was the training in pedagogy at the Federal University of Ceará . Through this study it was possible to rescue the history of pedagogy students at the level of Brazil and the Faculty of Education of the UFC , study on the design of monitoring applied in pedagogy courses of UFC and reflect the importance of monitoring program on vocation for teaching . Understanding how the monitoring was important for the student body opt for teaching in higher education becomes extremely important for the tutoring of the time was training to be a specialist in the school system . This research was done in a qualitative , descriptive and historiographical form . The first methodological step of the research will include analysis of documents and literature . In the second stage of the research semi- structured interviews were used . Monitoring , in the course of the text , it turned out, at that time , as fundamental to underpin the students in the teaching option . The monitoring was that opened the door to an experience hitherto overlooked. When the law was created , but had this goal oriented training for higher education . But not everything that is created in this country is applied in practice. And it was precisely this law that made the students and many other students who were monitors if firmassem the teaching career in higher education.